Adopsi Model UTAUT 2 : Penggunaan Teknologi QRIS Kopiria Samarinda - Risky, Risky; Bharata, Wira; Andriana, Ana Noor; Arsyad, Annisa Wahyuni (MDP Student Conference, 2024)
: This research aims to determine the intention and behavior of QRIS technology usage among consumers of Kopiria in Samarinda City through the UTAUT 2 research model by Visnawath Venkatesh. This type of research employs an explanatory research design. Data collection techniques involve distributing questionnaires with multiple questions that describe each indicator on the variables. The sampling technique is non-probability sampling through quota sampling method, with a total of 100 respondents. The data analysis technique used is the structural equation model (SEM) analysis with the assistance of Smart PLS 4 software. The results of this research indicate a positive influence of performance expectation, effort expectation, social influence, hedonic motivation, and price value on the behavioral intention and usage behavior. Four variables show significant values, namely performance expectation, social influence, and price value on behavioral intention, and behavioral intention on usage behavior.